The challenge of internal unity within the URCSA Cape regional synod : seeking to understand trust, fairness and loyalty - Tromp, Hendry Hesting (Stellenbosch : Stellenbosch University, 2022)
Thesis (MTh)--Stellenbosch University, 2022.